Seeing through God : a geophenomenology - Llewelyn, John, 1928- (Studies in Continental thought., 2004)
In Seeing Through God, John Llewelyn explores the act of looking in the wake of the death of the transcendent God of metaphysics. Taking up strategies developed by the Western sciences for seeing and observing, he finds the so-called tough-minded practices of the physical sciences are very much at home with the so-called tender-minded practices of Eastern religions. Instead of opposing East and West, Llewelyn thinks that blending these spheres leads to a better understanding of aesthetic experience and imagination. In this blending, he presents a phenomenological description of the imaginat.